Na+-H+ exchanger 1 determines atherosclerotic lesion acidification and promotes atherogenesis - Cong-Lin Liu (Nature Portfolio, 2019)
Na+-H+ exchanger 1 (Nhe1) regulates extracellular pH by extruding protons in exchange for extracellular Na+ . Here, Liu et al. show that Nhe1 promotes the development and acidification of atherosclerotic lesions and that pH-sensitive probes can be used to monitor plaque growth and acidification.